2022
DOI: 10.4028/p-1amod0
|View full text |Cite
|
Sign up to set email alerts
|

Development of Thermoplastic Composite Tube from HDPE/Barley Straw Fibers Using Extrusion Method

Abstract: This paper was devoted to the technological process of manufacturing a biocomposites tube made of low-density polyethylene and barley straw fibers. 50% of HDPE, 42% barley straw, 5% of shungite (mineral filler), 2% Maleid F (N, N-metaphenylenediamine) as coupling agent, and 1% Hexol CLA as lubricant were pre-mixed before compounding. The compounding of the raw materials was carried out on a co-rotating twin-screw extruder. The resulting granules were fed into the single screw extruder to obtain thermoplastic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, the effect of particle size of the used beverage cartons was not investigated. Previous studies reported that particle size of filler affects the mechanical properties of the polymer composites (Fu et al 2008;Aldousiri et al 2013;Deepak et al 2019;Delviawan et al 2019;Aranda-García et al 2020;Hubbe and Grigsby 2020;Sinha et al 2020;Kuzmin et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of particle size of the used beverage cartons was not investigated. Previous studies reported that particle size of filler affects the mechanical properties of the polymer composites (Fu et al 2008;Aldousiri et al 2013;Deepak et al 2019;Delviawan et al 2019;Aranda-García et al 2020;Hubbe and Grigsby 2020;Sinha et al 2020;Kuzmin et al 2022).…”
Section: Introductionmentioning
confidence: 99%